Measurement of spin correlation in top-antitop quark events and search for top squark pair production in pp collisions at √s = 8 TeV using the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; et al. (Physical review letters, 2015)
A measurement of spin correlation in t¯t production is presented using data collected with the ATLAS detector at the Large Hadron Collider in proton-proton collisions at a center-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 20.3  fb−1. The correlation between the top and antitop quark spins is extracted from dilepton t¯t events by using the difference in the azimuthal angle between the two charged leptons in the laboratory frame. In the helicity basis the measured degree of correlation corresponds to Ahelicity=0.38±0.04, in agreement with the standard model prediction. A search is performed for pair production of top squarks with masses close to the top quark mass decaying to predominantly right-handed top quarks and a light neutralino, the lightest supersymmetric particle. Top squarks with masses between the top quark mass and 191 GeV are excluded at the 95% confidence level.